The change of auditor: the portuguese case - Heliodoro, Paula (2018)
The existing problem around the change of auditor and the opinion issued by the auditor through the financial audit report has proved to be an important issue. The objective of this research is to examine to what extent the change of auditor is related to the type of opinion that the auditor expressed in the audit report. In pursuit of this objective was carried out an empirical study supported a sample from a set of entities with securities admitted to trading on the Portuguese stock market in the period between 2006 and 2012 (seven years) and used logistic regression to test whether the reception the modified financial audit report indicated the change of auditor. The findings point to the existence of a significant positive relationship between the qualified audit report and a change of auditor, verifiable for the reserves on assets and other, but not to the reserves on own and borrowed funds. The largest number of reserves occurs in the years 2007, 2009 and 2011, most of nature reserves is related to equity and assets, and the change of auditor is more associated with reserves on assets and other reserves than the reserves on own and borrowed funds.